Evaluasi Penggunaan Analgetik-Antipiretik pada Pasien Anak Demam Berdarah Dengue (DBD) di Instalasi Rawat Inap RSUP Dr. Soeradji Tirtonegoro Klaten Tahun 2014 - Hapsari, Sabrina Ayu (2016)
Dengue Hemorrhagic Fever (DHF) is an infectious disease which is caused by dengue virus. Patients with DHF using analgesic-antipyretic therapy to treat the high fever. The use of analgesic-antipyretic may cause bleeding and other worsen consequences. Some analgesic-antipyretics also are contraindicated for children. This study was aimed to evaluate the rational use of analgesic-antipyretic in pediatric inpatients with Dengue Hemorrhagic Fever (DHF) in General Hospital in 2014. This study is a non-experimental research with retrospective data retrieval. Samples were taken as many as 66 patients with purposive sampling method. This research was conducted by evaluating the rationality or the precision use of analgesic-antipyretics based on the right indications, the right patient, the right medication and the right dose, then adjusted by the guidelines of the World Health Organization (WHO) in 2011 and the standard of Pediatric Dosage Handbook 2009. The results showed the analgesic-antipyretic most widely used is Paracetamol which are used by 66 patients (100%). The results showed use of analgesic-antipyretic with the right indication were given to 53 patients (80,30%), right patient were given to 66 patients (100%), right drug were given to 66 patients (100%) and right dose were given to 51 patients (77,27%). Then, from this evaluation showed that 51 cases (77,27%) use of analgesic-antipyretic were rational.